Elaboração de software educacional para dimensionamento de ligações em madeira com pinos metálicos segundo eurocode 5 (2008) - Schawnz, Marcos Vinicius (2014)
Timber connections design remain one of the great challenges for engineers and architects. Detailing and designing timber connections can consume 50% until 80% of the time, even the connections execution can consume more than a half of the total building execution time. When performed manually, the calculation becomes complex and extensive, however, with the advance of computer science, it is possible to develop software to support this task, enabling the professional only validate the calculation results and concentrate on their analysis. The timber bolted connections constitutes one of the most useful and widespread joints in Brazil, considering that the steel bolts are responsible to transmit shear forces between the shear planes. The European Standard (EUROCODE 5) and Brazilian Standard (NBR 7190) show similar design procedure, developed through the same theory, although, the Brazilian design is more simplified, solving with precision only particular cases. Considering these particularities, emerged the aim of the development of a software for bolted connections design considering the European Standard Design Method, correctly adapted for the national conditionals of species, parcial factors and strength modification factors. The TCD (Timber Connections Design) software constitutes an important didactical tool and a dissemination way of the bolted connections design method, contributing for the development of timber construction field in the country.